Stages d'enseignement dans les commissions scolaires anglophones du Québec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Chaque année, le gouvernement provincial finance des expériences de formation supervisées en milieu scolaire pour les stagiaires en enseignement, appelées « stages d’enseignement ». Le présent résumé examine la répartition de ces fonds entre les neuf commissions scolaires anglophones en fonction de la proportion de stagiaires en enseignement qu’elles accueillent en provenance des universités québécoises. Les données mettent en évidence une concentration des stages d’enseignement dans les commissions scolaires situées à proximité des universités anglophones et dans le grand Montréal, ce qui désavantage certaines écoles en régions rurales et éloignées.

Student Teacher Practicums in English School Boards in Quebec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Each academic year the provincial government provides financial support for supervised, in-school training experiences for student teachers, known as teaching practicums. This brief examines how these funds are distributed across the nine English school boards based on the proportion of student teachers they host from Quebec universities. The data highlights a concentration of teaching practicums undertaken in school boards with proximity to English universities and Greater Montreal, thereby disadvantaging some rural and remote schools.

Inclusion des Québécois d’expression anglaise au Programme d’accès à l’égalité en emploi - Bourhis, Richard Y. (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Le Programme d’accès à l’égalité en emploi (PAÉE) du gouvernement du Québec cible cinq groupes vulnérables sous-représentés dans l’administration publique. La minorité anglophone ne fait pas actuellement partie de ces groupes. Toutefois, depuis plusieurs décennies, les anglophones ont connu un déclin de leur vitalité institutionnelle et économique, malgré des niveaux élevés d’accomplissement scolaire et un bilinguisme croissant. En comparaison avec les francophones, les anglophones se trouvent maintenant dans des conditions socio-économiques moins favorables, avec des salaires médians annuels inférieurs, ainsi que des taux de chômage et de pauvreté plus élevés dans la plupart des 17 régions administratives du Québec. De plus, ils déclarent subir davantage de discrimination et de linguicisme que la majorité francophone. Leur participation dans la fonction publique québécoise reste très faible (1 %) par rapport à leur proportion de 10% dans la population provinciale selon la langue maternelle. Compte tenu de ces éléments, il est recommandé d’envisager l’inclusion des Québécois d’expression anglaise comme groupe cible du PAÉE. Ce document de travail porte sur le PAÉE que la Commission des droits de la personne et des droits de la jeunesse (CDPDJ) administre pour 338 organismes publics.

Inclusion of English-speaking Quebecers in the Equal Access Employment Program - Bourhis, Richard Y. (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
The Quebec government’s Equal Access Employment Program (EAEP) targets five vulnerable, underrepresented groups in the public service. The anglophone minority is not currently one of them. However, in the past few decades, anglophones have experienced a decline in their institutional and economic vitality despite high levels of academic achievement and growing bilingualism. Compared with francophones, anglophones now live in less favourable socioeconomic conditions, with lower annual median incomes and higher unemployment and poverty rates in most of the 17 administrative regions of Quebec. They also report higher levels of discrimination and linguicism than the francophone majority. Their participation in Quebec’s public service remains very low (1%) when one considers that mother tongue anglophones make up 10% of the provincial population. In light of the above, we recommend considering including English-speaking Quebecers as an EAEP target group. This paper focuses on the EAEP that the Commission des droits de la personne et des droits de la jeunesse (CDPDJ) administers for 338 public organizations.

Proposal for Including English-speaking Quebecers in the Programme d'accès a l'égalité en emploi (PAÉE) - Bourhis, Richard Y. (2024)

Innovative Mentorship Program Equips English-Speaking Quebecers With Workplace French Skills - Provincial Employment Roundtable (PERT) (2024)

Un programme novateur de mentorat pour renforcer les compétences en français des Québécois d'expression anglaise en milieu de travail - Provincial Employment Roundtable (PERT) (2024)

Parcours d'apprenants en langues dans l'écosystème de la formation en français au Québec - Provincial Employment Roundtable (PERT) (2024)

User Journeys of Language Learners Navigating Québec's French Language Training System - Provincial Employment Roundtable (PERT) (2024)
In recent years, the Québec government has significantly invested in French language training programs to promote greater usage of French in workplaces, schools, and society. Alongside these efforts, public discourse has emerged about the perceptions French-speaking Quebecers hold of English speakers, many of whom believe that English speakers are not committed to learning or using French despite the availability of publicly funded French language training resources. To explore these issues, this study examines the experiences, motivations, and barriers faced by English-speaking individuals in the labour force regarding French language training, particularly following the introduction of new services by Francisation Québec in June 2023. In doing so, we develop a broad typology of different language learners and explore their language-learning journey through interviews regarding their experiences and perceptions of the French language, language training, and navigating Québec’s labour market. We also interview subject matter experts to identify types of language learners and key themes. We then discuss the impact that these different experiences have on language learners’ outcomes, as well as the types of policy and program approaches that could improve their experiences with adult French language training programs.

Appel à une action concertée pour lever les obstacles à l’emploi des Québécois d’expression dans la Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Gaspésie–Îles-de-la-Madeleine Experience the Highest Unemployment Rate in Québec, New Report Finds - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise de la Gaspésie-Îles-de-la-Madeleine connaissent le taux de chômage le plus élevé au Québec, selon un nouveau rapport - Provincial Employment Roundtable (PERT) (2024)

English Speakers in the Laurentides Face Growing Economic Challenges, New Report Shows - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise des Laurentides sont confrontés à des défis économiques croissants, selon un nouveau rapport - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Montérégie Facing Increased Unemployment and Ongoing Economic Disparities as Compared to Francophones - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise de la Montérégie font face à un taux de chômage accru et à des disparités économiques persistantes par rapport aux francophones - Provincial Employment Roundtable (PERT) (2024)

Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Les nouvelles données du recensement pour la région de la Côte-Nord n'indiquent aucune amélioration de la vitalité économique des Québécois d’expression anglaise depuis 2016 - Provincial Employment Roundtable (PERT) (2024)

New Census Data for Côte-Nord Shows No Improvement in the Economic Vitality of English Speakers Since 2016 - Provincial Employment Roundtable (PERT) (2024)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Caractéristiques sociodémographiques des minorités visibles - Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Gatineau.

Caractéristiques sociodémographiques des minorités visibles - Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Laval.

Caractéristiques sociodémographiques des minorités visibles - Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Longueil.

Caractéristiques sociodémographiques des minorités visibles - MRC L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC L'Assomption.

Caractéristiques sociodémographiques des minorités visibles - MRC La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC La Vallée-du-Richelieu.

Caractéristiques sociodémographiques des minorités visibles - MRC Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Les Moulins.

Caractéristiques sociodémographiques des minorités visibles - MRC Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Roussillon.

Caractéristiques sociodémographiques des minorités visibles - MRC Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Thérèse-De Blainville.

Caractéristiques sociodémographiques des minorités visibles - MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Vaudreuil-Soulanges.

Caractéristiques sociodémographiques des minorités visibles - Reste du Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

Caractéristiques sociodémographiques des minorités visibles - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Chaudière-Appalaches

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Abitibi-Témiscamingue.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Est-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Estrie – CHU de Sherbrooke.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Outaouais.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Capitale-Nationale

Caractéristiques sociodémographiques des minorités visibles - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Mauricie-et-du-Centre-du-Québec.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Centre.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Est.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Ouest.

Caractéristiques sociodémographiques des minorités visibles - RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Lanaudière.

Caractéristiques sociodémographiques des minorités visibles - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Laval.

Caractéristiques sociodémographiques des minorités visibles - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS des Laurentides.

Caractéristiques sociodémographiques des minorités visibles - RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Bas-Saint-Laurent.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Sud-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Nord-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Saguenay-Lac-Saint-Jean

Caractéristiques sociodémographiques des minorités visibles - Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Sherbrooke.

Caractéristiques sociodémographiques des minorités visibles - Ville de Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Québec.

Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Caractéristiques sociodémographiques des minorités visibles au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2024)
Number of pages: 12

Socio-Demographic Characteristics of Visible Minorities in Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Gatineau, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Laval, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in MRC de L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de L'Assomption.

Socio-Demographic Characteristics of Visible Minorities in MRC de La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de La Vallée-du-Richelieu.

Socio-Demographic Characteristics of Visible Minorities in MRC de Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Les Moulins.

Socio-Demographic Characteristics of Visible Minorities in MRC de Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Roussillon.

Socio-Demographic Characteristics of Visible Minorities in MRC de Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Thérèse-De Blainville.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec.

Socio-Demographic Characteristics of Visible Minorities in Québec City - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec City, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the rest of Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Chaudière-Appalaches.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Abitibi-Témiscamingue.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Est-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Estrie – CHU de Sherbrooke.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Outaouais.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Capitale-Nationale.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Centre.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Est.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Lanaudière.

Socio-Demographic Characteristics of Visible Minorities in RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Laval.

Socio-Demographic Characteristics of Visible Minorities in RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS des Laurentides.

Socio-Demographic Characteristics of Visible Minorities in RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Bas-Saint-Laurent.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Sud-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Nord-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Saguenay - Lac-Saint-Jean

Socio-Demographic Characteristics of Visible Minorities in Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Sherbrooke, which is considered a territory equivalent to an MRC.

Portrait of the Clientele : Qualitative Research - Advisory Commitee for English-Speaking Quebecers (2024)

Highlights of the Sociodemographic Profile of English-speaking Quebecers Aged 15-19 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Points saillants du profil sociodémographique des Québécois(es) d’expression anglaise de 15 à 29 ans - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Outaouais - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Outaouais - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Capitale-Nationale’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues English-speaking workers in Capitale-Nationale face, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Chaudière-Appalaches’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Chaudière-Appalaches, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Côte-Nord - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Côte-Nord’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Côte-Nord, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Gaspésie–Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Gaspésie-Îles-de-la-Madeleine’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Gaspésie-Îles-de-la-Madeleine, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Montérégie’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Montérégie, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Saguenay–Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Saguenay-Lac-Saint-Jean’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes by identifying some of the employment challenges and issues for English-speaking workers in Saguenay-Lac-Saint-Jean, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in the Laurentides - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Les Laurentides’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Les Laurentides, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Situation of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Profil d’emploi des Québécois d’expression anglaise de Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
Ce rapport a pour objectif de contribuer aux connaissances et à la compréhension de la situation en matière d’emploi au sein des communautés d’expression anglaise dans la région de Chaudière-Appalaches. Il examine les informations les plus complètes et actuelles sur les conditions démographiques et les états de la population active de ces communautés. Les sujets traités incluent le travail, le taux de chômage, le niveau de revenu et le niveau de scolarité afin d’offrir un portrait plus global de l’emploi et de l’employabilité des Québécois d’expression anglaise, qui sont une minorité linguistique dans la région. En plus d’examiner les données démographiques et la population active d’expression anglaise dans cette région, ce profil analyse les principales caractéristiques du marché du travail et des industries au sein desquelles les personnes d’expression anglaise travaillent. Le profil se termine en identifiant plusieurs des défis et des enjeux en matière d’emploi pour les travailleurs d’expression anglaise dans la Chaudière-Appalaches, et en offrant des recommandations préliminaires afin d’aider à améliorer leur situation sur le marché du travail.

Profil d’emploi des Québécois d’expression anglaise de la Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)
Ce rapport a pour objectif de contribuer aux connaissances et à la compréhension de la situation en matière d’emploi au sein des communautés d’expression anglaise dans la région de la Capitale-Nationale. Il examine les informations les plus complètes et actuelles sur les conditions démographiques et les états de la population active de ces communautés. Les sujets traités incluent le travail, le taux de chômage, le niveau de revenu et le niveau de scolarité afin d’offrir un portrait plus global de l’emploi et de l’employabilité des Québécois d’expression anglaise, qui sont une minorité linguistique dans la région. En plus d’examiner les données démographiques et la population active d’expression anglaise dans cette région, ce profil analyse les principales caractéristiques du marché du travail et des industries au sein desquelles les personnes d’expression anglaise travaillent. Le profil se termine en identifiant plusieurs défis et enjeux en matière d’emploi pour les travailleurs d’expression anglaise dans la Capitale-Nationale et en offrant des recommandations préliminaires afin d’aider à améliorer leur situation sur le marché du travail.

Profil d’emploi des Québécois d’expression anglaise de la Côte-Nord - Provincial Employment Roundtable (PERT) (2024)
Le présent rapport vise à approfondir la compréhension de la situation de l’emploi dans les communautés d’expression anglaise de la Côte-Nord, qui représentent des minorités linguistiques dans la région. Il s’agit d’une collecte de données les plus actuelles et complètes sur le contexte démographique de ce groupe et sa réalité sur le marché du travail. Les sujets traités – travail, taux de chômage, revenu, niveau de scolarité – ont pour but de brosser un portrait d’ensemble de l’emploi et de l’employabilité des Québécois·e·s d’expression anglaise (QEA) dans la région. En plus du contexte démographique et du visage de la population active des communautés d’expression anglaise de la Côte-Nord, le présent rapport examine les principales caractéristiques du marché du travail et des secteurs où travaillent ces groupes. À la toute fin, on présente certains défis et enjeux de l’emploi dans ces communautés ainsi que des recommandations préliminaires en vue d’améliorer les débouchés.

Profil d’emploi des Québécois d’expression anglaise de la Gaspésie–Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2024)

Profil d’emploi des Québécois d’expression anglaise de la Montérégie - Provincial Employment Roundtable (PERT) (2024)
Le présent rapport vise à approfondir la compréhension de la situation de l’emploi dans les communautés d’expression anglaise de la Montérégie, qui représentent des minorités linguistiques dans la région. Il s’agit d’une collecte de données les plus actuelles et complètes sur le contexte démographique de ce groupe et sa réalité sur le marché du travail. Les sujets traités – travail, taux de chômage, revenu, niveau de scolarité – ont pour but de brosser un portrait d’ensemble de l’emploi et de l’employabilité des Québécois·e·s d’expression anglaise (QEA) dans la région. En plus du contexte démographique et du visage de la population active des communautés d’expression anglaise de la Montérégie, le présent rapport examine les principales caractéristiques du marché du travail et des secteurs où travaillent ces groupes. À la toute fin, on présente certains défis et enjeux de l’emploi dans ces communautés ainsi que des recommandations préliminaires en vue d’améliorer les débouchés.

Profil d’emploi des Québécois d’expression anglaise des Laurentides - Provincial Employment Roundtable (PERT) (2024)
Ce rapport a pour objectif de contribuer aux connaissances et à la compréhension de la situation en matière d’emploi au sein des communautés d’expression anglaise des Laurentides, qui constituent une minorité linguistique dans la région. Il examine les informations les plus récentes et les plus complètes sur leur situation démographique et leur situation par rapport à la population active. Les sujets traités comprennent le travail, le taux de chômage, le niveau de revenu et le niveau de scolarité des travailleurs afin d’offrir un portrait plus global de l’emploi et de l’employabilité des Québécois d’expression anglaise. En plus d’examiner les données démographiques et la population active d’expression anglaise de cette région, ce profil analyse également les principales caractéristiques du marché du travail et des industries au sein desquelles les personnes d’expression anglaise travaillent. Le profil se termine en identifiant plusieurs défis et enjeux en matière d’emploi pour les travailleurs d’expression anglaise dans les Laurentides, et en offrant des recommandations préliminaires afin d’aider à améliorer leur situation sur le marché du travail.

Profil d’emploi des Québécois d’expression anglaise du Saguenay–Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2024)
Le présent rapport vise à approfondir la compréhension de la situation de l’emploi dans les communautés d’expression anglaise du Saguenay–Lac-Saint-Jean, qui représentent des minorités linguistiques dans la région. Il s’agit d’une collecte de données les plus actuelles et complètes sur le contexte démographique de ce groupe et sa réalité sur le marché du travail. Les sujets traités – travail, taux de chômage, revenu, niveau de scolarité – ont pour but de brosser un portrait d’ensemble de l’emploi et de l’employabilité des Québécois·e·s d’expression anglaise (QEA) de la région. En plus du contexte démographique et du visage de la population active des communautés d’expression anglaise du Saguenay, le présent rapport examine les principales caractéristiques du marché du travail et des secteurs où travaillent ces groupes. À la toute fin, on présente certains défis et enjeux de l’emploi dans ces communautés ainsi que des recommandations préliminaires en vue d’améliorer les débouchés.

Propositions prébudgétaire 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
La Table ronde provinciale de l'emploi (PERT) a le plaisir de soumettre ce mémoire et proposition aux consultations prébudgétaires 2024-25 du ministère des Finances. Fondée en 2020, PERT est une organisation à but non lucratif qui se consacre aux problèmes d'emploi et d'employabilité auxquels sont confrontées les communautés d’expression anglaise du Québec. Depuis sa création, PERT est devenu le principal porte-parole des solutions aux problèmes d'emploi des Québécois d’expression anglaise. Grâce à son travail de recherche et de coordination des parties prenantes, PERT a publié plus de 25 rapports qui décrivent les problèmes et les besoins des Québécois d’expression anglaise en matière d'emploi dans les 17 régions de la province. PERT compte parmi ses plus de 90 membres des prestataires de services d'emploi, des établissements d'enseignement, et des organisations régionales et employeurs. La situation d'emploi de la population d’expression anglaise du Québec continue de se détériorer, comme en témoignent les taux de chômage plus élevés et les obstacles liés à la langue française auxquels les Québécois d’expression anglaise sont confrontés sur le marché du travail québécois. Dans ce mémoire, nous identifions deux facteurs clés qui contribuent aux défis continus des Québécois d’expression anglaise en matière d'emploi : le manque de services et de programmes d'emploi ciblés pour les Québécois d’expression anglaise et le manque de programmes de formation en français intégrés au travail pour les aider à entrer sur le marché du travail et à y rester. Les difficultés économiques et d'emploi des Québécois d’expression anglaise s'inscrivent dans le contexte plus large des vents contraires auxquels le Québec est confronté, notamment les pénuries de main-d'oeuvre sans précédent, le déclin démographique et les problèmes liés à l'attraction et à la rétention des talents. Ce mémoire résume les résultats de la recherche de PERT, en particulier les défis en matière d'emploi auxquels est confrontée la communauté d’expression anglaise du Québec, et propose des recommandations pour le prochain budget qui permettront de relever ces défis et de créer un Québec plus productif, plus inclusif et plus prospère pour tous.

Situation d’emploi des personnes d'expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by the Secrétariat aux relations avec les Québécois d’expression anglaise from December 2021 to the present. Founded in 1979, Townshippers’ Association is mandated to promote the interests ofthe ESC in the historical Eastern Townships, strengthening the cultural identity of thiscommunity, and encouraging the full participation of the English-speaking population in the community at large. Townshippers’ Association’s projects address heritage andculture, community development, access to health and social services, support for seniors, and youth retention. The Secretariat aux relations avec les Québécois d’expression anglaise is responsible forensuring that the concerns of English-speaking Quebecers are taken into account ingovernment orientations and decisions in collaboration with government ministries and bodies.

Searching for a Work-Life Balance in Your Health and Social Services Career? - Townshippers' Association; Dialogue McGill (2024)

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)
Number of pages: 12

Socio-demographic Profile of the Population Aged 55 and Over : Province of Quebec - Pocock, Joanne (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)
Number of pages: 12

Press Release: New study reveals economic precarity and limit job supports for racialized communities and English-speaking immigrants in Québec. - Provincial Employment Roundtable (PERT) (2023)

Une nouvelle étude révèle la précarité économique et l’insuffisance des aides à l’emploi pour les communautés racialisées et les immigrants d’expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2023)

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)
Number of pages: 8

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)
Number of pages: 12

Mapping Employment Supports for Québec's Racialized and Immigrant English-speaking Communities - Gagnon, Morgan; Kuzviwanza, Sta (Provincial Employment Roundtable (PERT), 2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)
Number of pages: 8

Au Québec et ailleurs : Un examen des approches nationales et internationales en matière de formation linguistique pour les adultes - Provincial Employment Roundtable (PERT) (2023)
Depuis les années 1970, le gouvernement québécois a investi massivement dans la création et la mise en oeuvre de programmes de francisation. En 2022, le Québec a modifié la Charte de la langue française et s’est engagé à élargir l’offre de services de francisation aux adultes, dans le but d’amener ce groupe à un niveau de français suffisant. En plus de bénéficier de nouveaux investissements, la francisation des adultes a fait l’objet d’un réexamen public de son efficacité, de sa qualité et de son accessibilité dans la province. Il s’agit de mesures particulièrement importantes, étant donné que le français est la langue de travail au Québec et que les personnes qui manient mal cette langue risquent de rencontrer des obstacles sur le marché de l’emploi. La présente étude vise à contribuer à l’amélioration de l’écosystème québécois de la francisation des adultes. Pour ce faire, elle examine comment différentes administrations au Canada et à l’étranger ont déployé ce type de formation sur leur territoire. Bien que le paysage linguistique unique du Québec ne soit pas parfaitement transposable dans un autre contexte, il peut s’avérer utile d’analyser ce qui se fait ailleurs pour cerner des innovations et des approches en matière de politiques applicables dans la province. Le présent rapport explore les approches en matière de formation linguistique aux adultes au Nouveau-Brunswick, en Ontario, au pays de Galles, en Catalogne, dans la Communauté autonome basque et, enfin, en Finlande. Des travaux de recherche secondaire et des entrevues qualitatives avec des spécialistes ont servi à brosser, pour chaque région, le portrait du cadre de formation linguistique aux adultes financé par le gouvernement. L’accent a été mis sur les programmes de langue pour les personnes sur le marché du travail, dans l’optique d’examiner comment les différentes régions répondent aux priorités d’aménagement linguistique et d’intégration au marché du travail. Nous avons analysé la situation et les expériences propres à chaque région pour formuler des recommandations à l’intention des responsables politiques et des autres parties prenantes du Québec.

Cartographie des aides à l'emploi pour les communautés racialisées et immigrantes d'expression anglaise du Québec - Provincial Employment Roundtable (PERT) (2023)
L'emploi est de plus en plus devenu une question prioritaire pour les communautés d’expression anglaise du Québec, qui continuent d'être confrontées à des taux de chômage plus élevés et à des revenus plus faibles que la majorité francophone. Les données sur la population active concernant les immigrants d'expression anglaise et les personnes racialisées indiquent que ces groupes ont tendance à éprouver des difficultés encore plus grandes sur le marché du travail. Étant à la fois minorités linguistiques et immigrants et/ou personnes racialisées, elles naviguent sur un marché du travail francophone tout en faisant face à des défis tels que la discrimination et le manque de ressources. Dans ce contexte, les aides à l'emploi, telles que les ateliers d'employabilité, l'aide à la recherche d'emploi et l'accompagnement professionnel, jouent un rôle important dans la lutte contre les obstacles au marché du travail. Pour les immigrants d’expression anglaise et les personnes racialisées, les aides à l'emploi qui reconnaissent leurs expériences uniques et leur position sur le marché du travail peuvent avoir un impact positif sur leurs résultats sur le marché du travail. Cette recherche vise à mieux comprendre la situation des immigrants et des Québécois d’expression anglaise racialisés sur le marché du travail au Québec et à évaluer les mesures de soutien à l'emploi disponible pour ces communautés.

Press Release : New Report Highlights the Best Practices for French-language Education in Québec - Provincial Employment Roundtable (PERT) (2023)

Un nouveau rapport met en lumière les meilleures pratiques en matière d’éducation en langue française au Québec - Provincial Employment Roundtable (PERT) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 11

Provincial Employment Roundtable : Québec and the rest: A survey of national and international approaches to adult language training - Kuzviwanza, Sithandazile; Holt, Cimminnee (Provincial Employment Roundtable (PERT), 2023)

Apprendre le français à l’âge adulte : Examen des pratiques exemplaires actuelles en francisation des adultes au Québec - Provincial Employment Roundtable (PERT) (2023)
L’apprentissage du français représente un défi pour beaucoup de minorités linguistiques au Québec. Vu la primauté grandissante du français dans la province, l’apprentissage de cette langue est une priorité de plus en plus importante pour les personnes qui sont confrontées à des obstacles liés au français et qui souhaitent participer au marché du travail et à la société québécoise dans son ensemble. La Table ronde provinciale sur l’emploi (PERT) s’est déjà penchée sur l’écosystème québécois de la francisation des adultes pour se faire une idée de la disponibilité et de l’accessibilité des programmes offerts dans la province. Nos constats : le cadre québécois de francisation des adultes est une mosaïque de programmes à la disponibilité et aux coûts variables, et d’importants obtacles se dressent devant les personnes apprenantes selon leur lieu de vie, leur statut migratoire et leur statut d’emploi, entre autres critères d’admissibilité. Par ailleurs, si la formation linguistique offre des avantages concrets, la recherche montre que les adultes peuvent avoir plus de difficulté que les jeunes à apprendre une langue. En effet, les adultes ont besoin de plus de temps et d’investissement pour progresser, et ont souvent plusieurs engagements simultanés (travail, proche aidance). Compte tenu des caractéristiques propres à l’apprentissage d’une langue chez les adultes, l’élaboration et la mise en oeuvre de programmes connexes nécessitent une attention particulière. Par la présente étude, nous souhaitons contribuer à l’amélioration des programmes de francisation des adultes au Québec. L’étude donne un aperçu des pratiques exemplaires en la matière sur la base d’entrevues menées auprès de vingt-quatre (24) éducateurs, éducatrices, cadres, chercheurs et chercheuses dont le travail vise à améliorer la francisation des adultes, et de travaux de recherche secondaire évalués par les pairs et les paires sur l’apprentissage d’une langue. Nous nous concentrons sur la francisation des Québécois d’expression anglaise, particulièrement ceux et celles qui rencontrent des obstacles à l’emploi d’ordre linguistique.

Communiqué de presse : L’écart de chômage entre les Québécois d’expression anglaise et les francophones au Québec a doublé, selon les données du nouveau recensement - Provincial Employment Roundtable (PERT) (2023)

Press Release : The Unemployment Gap Between English Speakers and French Speakers in Québec has Doubled, New Census Data Reveals - Provincial Employment Roundtable (PERT) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)
Number of pages: 16

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

La CEDEC a bon espoir que le plan d'action pour les langues officielles aura un effet à long terme et fera une importante différence sur la vitalité de la communauté d'expression anglaise du Québec - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 9

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

They “Could Care for Our Elderly in Our Homes” : The Historical Impact of Black Caregivers - Williams, Dorothy W. (2023)
My aim is to interrogate prevalent assumptions about health and social services through a survey of notable chapters in the history of Black caregiving in Quebec. The assumptions have created expectations and a false narrative built upon historical myths and erasures that undergird the provincial population’s understanding of its relationship with Black caregivers. Blacks, both Francophone and Anglophone, though not exclusively so, have had significant connection to the care and well-being of Quebec’s residents. Black caregiving in Quebec is not recent—indeed, Black caregivers have been intimately tied to Quebec’s labour force aspirations and development for centuries. Even so, it is rarely acknowledged, to the point of being virtually unknown. This paper seeks to address those gaps in the narrative by presenting a timeline dating back to the 17th century. It will reveal intricate connections between the different periods when it comes to segregation, prejudice, migration, immigration quotas, and bans.
Parallel title: QUESCREN Working Paper no. 10

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 12

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 12

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 13

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)
Number of pages: 8

Les Québécois d’expression anglaise connaissent un taux de chômage plus élevé et gagnent moins que leurs homologues francophones - Provincial Employment Roundtable (PERT) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 7

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 5

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)
Number of pages: 12

Employment Services - Assistance and Referral Centre (ARC) (2023)

Investing in the Vitality of English-speaking Quebec / Investir dans la vitalité du Québec d'expression anglaise - Community Health and Social Services Network (CHSSN) (2023)
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities of Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities of Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities, Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Abitibi-Témiscamingue and MRC Abitibi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Centre-du-Québec and MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC La Nouvelle-Beauce - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Lotbiniére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Côte-Nord and MRC Caniapiscau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Côte-Nord and MRC Le Golfe-du-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and les Îles-de-la-Madeleine - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Avignon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Bonaventure - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC La Côte-de-Gaspé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and MRC Le Rocher Percé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Maurice and la Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Montérégie and Longueuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and MRC La Vallée-de-la-Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Outaouais and MRC Les Collines-de-l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2021-2022 - Provincial Employment Roundtable (PERT) (2023)

Annual Report 2022-2023 - Provincial Employment Roundtable (PERT) (2023)

Brief : Public Consultation on the Government Action Plan to Combat Poverty and Social Exclusion - Provincial Employment Roundtable (PERT) (2023)
Québec is home to more than 1.2 million English speakers, representing 14.9% of the province’s population. Data from the 2021 Census of Canada indicates that English-speaking Quebecers occupy a more precarious economic position than their French-speaking counterparts, experience higher rates of poverty and unemployment and earn lower median incomes. Research conducted by PERT has highlighted some of the specific barriers and challenges English speakers face regarding labour market integration and retention in Québec, including lack of French-language training for the workforce, lack of English-language employability services, lack of English-language vocational training, and lack of wrap-around support services. These employment challenges impact English speakers' labour market outcomes and are associated with higher rates of poverty.1 Furthermore, many of these challenges, especially the lack of wrap-around supports (e.g. housing or food security), can directly contribute to – and result from – poverty.

Census 2021 Update : A Brief Review of the Latest Data on Employment Among Québec’s English Speakers - Provincial Employment Roundtable (PERT) (2023)
A review of the most recent census data on the employment situation of Québec’s English-speaking communities reveals that English speakers continue to experience significant challenges in Québec’s labour market. Despite a high rate of labour force participation and increases in educational attainment, English speakers in most regions of Québec face higher unemployment rates, lower median incomes and higher rates of poverty compared to the French-speaking majority. This report provides an overview of key labour market characteristics for Québec’s English-speaking communities based on data from the 2021 Census.

Mémoire : Consultation publique pour le plan d'action gouvernemental de lutte contre la pauvreté et l'exclusion sociale - Provincial Employment Roundtable (PERT) (2023)
Le Québec compte plus de 1,2 million de Québécois d’expression anglaise, soit 14,9 % de la population de la province. Les données du recensement du Canada de 2021 indiquent que les Québécois d’expression anglaise occupent une position économique plus précaire que leurs homologues francophones, qu'ils connaissent des taux de pauvreté et de chômage plus élevés et qu'ils gagnent des revenus médians plus faibles. Les recherches menées par PERT ont mis en évidence certains des obstacles et défis spécifiques auxquels sont confrontés les Québécois d’expression anglaise en matière d'intégration et de rétention sur le marché du travail au Québec, notamment le manque de formation en français pour the marché du travail, le manque de services d'employabilité en anglais, le manque de formation professionnelle en anglais et le manque mesures de soutien globales. Ces difficultés d'emploi ont un impact sur les résultats des Québécois d’expression anglaise sur le marché du travail et ont été associées à des taux de pauvreté plus élevés.1 En outre, nombre de ces difficultés, en particulier l'absence de services d'accompagnement (par exemple, le logement ou la sécurité alimentaire), peuvent directement contribuer à la pauvreté et en résulter.

Mémoire : Réflexion sur l'avenir de la langue française - Provincial Employment Roundtable (PERT) (2023)

Mise à jour du recensement 2021 : Une brève revue des dernières données sur l'emploi des Québécois d’expression anglaise du Québec - Provincial Employment Roundtable (PERT) (2023)
Un examen des données de recensement les plus récentes sur la situation de l'emploi des communautés d’expression anglaise au Québec révèle que les Québécois d’expression anglaise continuent de faire face à des défis importants sur le marché du travail. Malgré un taux élevé de participation à la population active et une augmentation du niveau de scolarité, les Québécois d’expression anglaise de la plupart des régions administratives de la province sont confrontés à des taux de chômage plus élevés, à des revenus médians plus faibles et à des taux de pauvreté plus élevés que ceux de la majorité francophone. Ce rapport donne un aperçu des principales caractéristiques du marché du travail des communautés d’expression anglaise au Québec, en se fondant sur les données du recensement de 2021.

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

Resolution 2023-06 : Support School Employees - Quebec Federation of Home and School Associations (QFHSA) (2023)
Parallel title : Resolutions Adopted at the 2023 Annual General Meeting

Health and Social Services Career Opportunities Training Guide : Eastern Townships Region - Townshippers' Association; Dialogue McGill (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 13

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 15

Enquête de 2021 sur l’emploi auprès des Québécois(es) et des organisations d’expression anglaise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport expose les expériences des Québécois·e·s d’expression anglaise dans la province au regard de l’emploi ainsi que les différents enjeux rencontrés et les besoins éprouvés par cette population sur le marché du travail. Désignée « communauté linguistique minoritaire officielle » du Québec, la population québécoise d’expression anglaise est toutefois caractérisée par une réelle diversité identitaire, comportant ainsi une pluralité de sous-communautés qui ne connaissent pas toutes les mêmes défis. Des points de convergence néanmoins existent, notamment du point de vue du statut socioéconomique de la communauté d’expression anglaise prise dans son ensemble. De fait, en dépit du statut d’élite socioéconomique qu’occupaient historiquement les personnes d’expression anglaise au Québec, la communauté actuelle est dans son ensemble caractérisée, en comparaison d’avec la majorité linguistique d’expression française, par des taux élevés de chômage et de plus faibles revenus. Ce rapport s’appuie des données provenant d’une enquête réalisée en deux volets. Le premier volet consistait à sonder 259 Québécois·e·s d’expression anglaise à propos de leur relation au marché du travail, de leur niveau de français, des répercussions de la pandémie et des obstacles à leur accès au marché du travail. À cette première enquête venait s’ajouter une seconde s’intéressant aux points de vue de 29 organisations qui emploient des personnes d’expression anglaise et servent leurs intérêts, quant au paysage de l’emploi pour cette population, et aux effets sur l’emploi des politiques linguistiques promouvant le français.

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 9

Communiqué de presse : Les programmes de formation professionnelle et technique offrent des voies d’accès à l’acquisition de la langue française pour les anglophones du Québec - Provincial Employment Roundtable (PERT) (2022)

Vocational and Technical Training Programs Offer Pathways to French-language Acquisition for Québec’s English Speakers - Provincial Employment Roundtable (PERT) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)
Number of pages: 8

Communiqué de presse : Le manque d'opportunités de formation en français pour les ordres professionnels contribue à la pénurie sur le marché du travail - Provincial Employment Roundtable (PERT) (2022)

Lack of French-Language Training Opportunities for Professional Orders Contributes to Labour Market Shortage - Provincial Employment Roundtable (PERT) (2022)

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

List of Employers in Quebec City Region with Jobs That Require English Skills - Voice of English-speaking Quebec (VEQ) (2022)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)
Number of pages: 8

English-speaking Québecers Experience Higher Unemployment and Earn Lower Incomes than their Francophone Counterparts - Provincial Employment Roundtable (PERT) (2022)

Committee Examines Rules for Posting Bilingual Positions - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Policy Matters Blog 8 – Bill 96

La commission examine les règles relatives à l’affichage des postes bilingues - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Question de politique – Blogue no8 (Projet de loi 96)

Committee Discusses Use of French in Professional Orders and the Workplace - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Policy Matters Blog 7– Bill 96

La commission discute de l’utilisation du français par les ordres professionnels et en milieu de travail - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Question de politique – Blogue no7 (Projet de loi 96)

Not Your Typical Self-Care Seminar : Prioritizing Connection Over Information - Joanisse, Mélanie (2022)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

Directory of Lawyers, Accountants, Notaries, & Real Estate : 2nd Edition - Cyr, Cathy; Wright, Tonya; Dade, Samantha (2022)

French-language Support for Québec's English-speaking Professionals - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
French-language barriers can be a challenge for professionals who are English speakers and must practice their profession in accordance with French-language policies. Despite high levels of English-French bilingualism among Québec’s English speakers, French remains a challenge for some who require additional profession-specific French-language training. Not only is French-language proficiency a requirement for membership in Québec’s professional orders, but professionals who do not meet language criteria must also pass a French-language competency exam administered by the Office québécois de la langue française (OQLF). Additionally, professional orders can mandate all their members to take French-language professional competency exams throughout their careers.

Soutien en langue française pour les professionnelles et professionnels d'expression anglaise au Québec - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
La langue française peut représenter un obstacle pour les professionnelles et professionnels d’expression anglaise qui doivent exercer leur profession en respectant les politiques linguistiques en place. Malgré un haut niveau de bilinguisme parmi les Québécois·e·s d’expression anglaise, le français demeure une embuche pour certain∙e∙s. Ces personnes professionnelles bénéficieraient de formation linguistique additionnelle en lien avec leur métier. Non seulement la maîtrise du français est un prérequis pour se joindre aux ordres professionnels québécois, mais, dans certains cas, les personnes qui ne satisfont pas aux critères linguistiques doivent aussi passer un examen de français de l’Office québécois de la langue française (OQLF). En outre, les ordres professionnels peuvent demander à leurs membres de se soumettre, durant leur carrière, à des examens de compétences linguistiques en français.

Booklet for Young Workers : Everything you Need to Know for your First Job - Montérégie West Community Network (MWCN); Educaloi (2022)

2021 Employment Survey of English-speaking Quebecers and Organizations - Provincial Employment Roundtable (PERT) (2022)
This report explores the employment experiences of English speakers in Québec as well as the issues and needs they face when it comes to navigating the labour market. English-speaking Quebecers, who are Québec’s official language minority community, sit at the intersections of various identities and communities from which diverse challenges and opportunities arise. At the same time, there are shared experiences of being an English speaker in Québec. One of them is the socioeconomic status of the English-speaking community as a whole. Despite the historical position of English speakers as a socioeconomic elite in Québec, today’s English-speaking community is collectively characterized by higher unemployment rates and lower incomes when compared to the French-speaking majority.

Bill 96 & Employment of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
On May 24, 2022, Québec’s National Assembly passed Bill 96, An Act Respecting French, the Official and Common Language of Québec. The bill, which presents significant modifications to The Charter of the French Language (Bill 101), as well as other existing legislation, was passed more than a year after it was introduced. On June 1, 2022, Bill 96 received royal assent and some of its clauses came into effect immediately. Other clauses of the bill will come into effect at later dates.

Employment Profile of English Speakers in Abitibi-Témiscamingue - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Abitibi-Témiscamingue’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Abitibi-Témiscamingue’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Bas-Saint-Laurent - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Bas-Saint-Laurent’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Bas-Saint-Laurent’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Centre-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Chaudière-Appalaches’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Chaudière-Appalaches’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Côte-Nord - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Côte-Nord’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Côte-Nord’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Estrie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Estrie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Estrie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Gaspésie-Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by GaspésieÎles-de-la-Madeleine’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Gaspésie-Îles-de-la-Madeleine’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Lanaudière - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Lanaudière’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Lanaudière’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Laurentides - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by English-speaking communities in the Laurentides by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys the economic structure of the Laurentides, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Laval - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Laval’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Laval’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Mauricie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Mauricie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Mauricie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Montérégie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Montérégie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Montréal - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Montréal’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Montréal’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Nord-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Nord-du-Québec’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Nord-du-Québec’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Outaouais - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Outaouais’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Outaouais’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Employment Profile of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
A review of available data on the employment status of English speakers in Québec reveals that English speakers — who represent 13.8% of Québec’s population and 14.3% of its labour force — face considerable challenges in the labour market. English speakers in most regions of Québec have higher unemployment rates and lower aftertax median incomes compared to French speakers, who represent 85.3% of the population.

Employment Profile of English Speakers in Saguenay-Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Saguenay-Lac-Saint-Jean’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Saguenay-Lac-Saint-Jean’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

English-Language Vocational and Technical Training in Québec - Provincial Employment Roundtable (PERT) (2022)
In recent years, there has been a renewed interest in the role of vocational and technical training in meeting urgent labour market needs, as well as the broader economic and social benefits it provides to individuals and societies. Vocational and technical training (VTT), which aims to equip students with hands-on skills for direct entry into the labour market, is offered at the secondary and college level in Québec. The majority of Québec’s VTT programs are offered in French and primarily serve the French-speaking majority in Québec, who represent 85.3% of the province’s population. There is a smaller ecosystem of English-language VTT programs, which are offered primarily to Québec’s English speakers, who account for 13.8% of the population.

Formation professionelle et technique en anglais au Québec - Provincial Employment Roundtable (PERT) (2022)
Dans les dernières années, la formation professionnelle et technique (FPT) suscite beaucoup d’intérêt, notamment pour son potentiel de combler les besoins urgents du marché du travail. Ses avantages économiques et sociaux, tant pour les individus que pour la société en général, font l’objet d’un engouement renouvelé. La formation professionnelle et technique vise à outiller la population étudiante de compétences concrètes leur permettant d’intégrer rapidement le marché du travail. Au Québec, elle est offerte aux niveaux secondaire et collégial. La plupart des programmes de FPT québécois se déroulent en français et s’adressent à un public d’expression française qui, rappelons-le, représente la majorité (85,3 %) des Québécois∙e∙s. Il existe malgré tout un petit écosystème de programmes de FPT en anglais, destiné principalement aux personnes québécoises d’expression anglaise (qui correspondent à 13,8 % de population totale de la province).

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Profil d'emploi des Québécois d'expression anglaise à Lanaudière - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de Lanaudière en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de Lanaudière, de même que l’activité professionnelle, le revenu et le niveau de scolarité des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise au Capitale-Nationale - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de la Capitale-Nationale en analysant les informations les plus complètes sur la démographie et les conditions de travail des des membres de la collectivité. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de la Capitale- Nationale, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but de dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise au Centre-du-Québec - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise du Centre-du-Québec en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise du Centre-du-Québec. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Centre-du-Québec, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise au Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de Chaudière-Appalaches en analysant les informations les plus complètes sur la situation démographique et la situation sur le marché du travail des personnes d’expression anglaise de Chaudière-Appalaches. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil étudie également la structure économique de Chaudière-Appalaches, ainsi que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs, dans le but de dresser un portrait d’emploi et d’employabilité plus global.

Profil d'emploi des Québécois d'expression anglaise au Nord-du-Québec - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise du Nord-du-Québec en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Nord-du-Québec, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2022)
Une révision des données disponibles sur le statut d’emploi des Québécois d’expression anglaise au Québec révèle que les Québécois d’expression anglaise — qui représentent 13.8% de la population du Québec et 14.3% de sa population active — font face à des difficultés considérables sur le marché du travail. Les Québécois d’expression anglaise dans la majorité des régions du Québec connaissent un taux de chômage supérieur et un revenu médian net inférieur aux francophones, qui représentent pour leur part 85.3% de la population.

Profil d'emploi des Québécois d'expression anglaise aux Laurentides - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise des Laurentides en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique des Laurentides, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de Bas-Saint-Laurent - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaises du Bas-Saint-Laurent en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de cette région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Bas-Saint-Laurent, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de Gaspésie-Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de Gaspésie-Îles-de-la-Madeleine en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de Gaspésie-Îles-de-la-Madeleine, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de la Côte-Nord - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de la Côte-Nord en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de la Côte-Nord, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de la Montérégie - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de la Montérégie en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de la Montérégie, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de la Montréal - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés de l’expression anglaise de Montréal en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de Montréal, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de Laval - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés de l’expression anglaise de Laval en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de Laval, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise de Saguenay-Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés de l’expression anglaise du Saguenay-Lac-Saint-Jean en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Saguenay-Lac-Saint-Jean, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise en Abitibi-Témiscamingue - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de l’Abitibi-Témiscamingue en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de cette région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de l’Abitibi-Témiscamingue, de même que le travail, le revenu et le niveau de scolarité des travailleurs dans le but de dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise en Estrie - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de l’Estrie en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de l’Estrie. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de l’Estrie, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise en Mauricie - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de la Mauricie en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de cette région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de la Mauricie, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Profil d'emploi des Québécois d'expression anglaise en Outaouais - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de l’Outaouais en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de l’Outaouais. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de l’Outaouais, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Programmes de francisation de la main-d'oeuvre au Québec : Évaluation des programmes de francisation de la main-d'oeuvre québécoise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport se penche sur l’état des programmes de francisation pour la main-d’oeuvre (PFMO) au Québec. Les PFMO sont des cours de français spécifiquement conçus pour accroître l’intégration des apprenantes et apprenants de langues sur le marché du travail en étant axés sur le vocabulaire et les compétences linguistiques qui contribuent à leur employabilité. Dans ce rapport nous avons recensé les PFMO offerts aux apprenantes et apprenants de langue française, et relevé les besoins clés, les lacunes et les possibilités d’amélioration au sein de l’écosystème.

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2022)

Comparing Unemployment Rates Among Québec's English and French Speakers by Education Level - Dufour, Caroline (2021)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Resolution 2021-07 : Addressing the Issue of the Teacher Shortage in Quebec - Quebec Federation of Home and School Associations (QFHSA) (2021)

Youth Entrepreneurship Guide - Fequet, Shelley; Fequet, Latesha; Roberts, Ashley (Coasters Association, 2021)
This guide is intended for young adults between the ages of 18-35. Its purpose is to help guide and support individuals through the process of creating their own business and to identify the resources needed to be successful. The development of this guide was supported by the members of the HOME Committee. Partners represented on the HOME Committee include; Community Economic Development and Employability Committee (CEDEC), Centre de services scolaire du Littoral. Centre lntegre de Sante et de Services Sociaux de la Cote-Nord (CISSS), Coasters Association and the MRC du Golfe-du-Saint-Laurent.

Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Skill-Building & Networking in the Time of COVID-19 - Khamala, Maya (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

Nord-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Chaudière-Appalaches - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Abitibi-Témiscamingue - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Outaouais - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Capitale-Nationale - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Côte-Nord - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Gaspésie - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Centre - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Est - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Ouest - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Lanaudière - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Laval - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Îles - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Laurentides - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Bas-Saint-Laurent - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Black in Quebec - Davids, John; Fang, Xiaoyan; Bramble, Shania (2021)

2nd Annual General Meeting 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report 2020-2021 - Regional Development Network (RDN) (2021)

East Island Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Rapport annuel 2020-2021 - Youth Employment Services (YES) (2021)
En qualité d’organisme sans but lucratif, YES contribue à l’enrichissement de la communauté en offrant des services de soutien en anglais pour aider les québécois à trouver un emploi ou démarrer ou développer leurs entreprises. Depuis plus de 25 ans, YES Emploi + Entrepreneuriat facilite l’accès à différentes opportunités de croissance auprès de la communauté d’expression anglaise du Québec. Célébrer le 25e anniversaire de notre organisation en pleine pandémie nous rappelle à quel point nos services d’accompagnement à l’emploi et d’aide aux entreprises sont d’une importance vitale.

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

Program Book - Youth Employment Services (YES) (2020)
issued: January, 2020/December, 2020

YES Program Book - Youth Employment Services (YES) (2020)
issued: September, 2020/December, 2020

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).
Parallel title: Report : Key Insights and Takeaways

Forum sur les perspectives jeunesse : orientations professionnelles et éducatives dans le monde post-COVID-19 - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
La jeunesse va (globalement) bien ! Ce message a été exprimé haut et fort lors d’une discussion captivante entre intellectuels, éducateurs, étudiants et conférenciers passionnés, qui s’est tenue virtuellement le 25 octobre 2020 dans le cadre du Forum sur les perspectives jeunesse de l’Université Concordia. L’événement a eu lieu à l’initiative du Réseau de recherche sur les communautés québécoises d’expression anglaise, par l’entremise de sa Table d’éducation interordres et en collaboration avec Youth 4 Youth Québec et le Centre de ressources de la communauté noire. Cette année, le forum avait un thème bien particulier : Orientations professionnelles et éducatives dans le monde post-COVID-19. En résumé, l’occasion a été donnée aux étudiants de saisir les nou- velles réalités de ce « monde d’après » afin qu’ils sachent comment s’engager sur la voie parfois déconcertante qui s’ouvre à eux. Alerte au divulgâcheur : tout va bien aller (mais il nous faudra procéder à quelques ajustements).
Parallel title: Rapport sue les idées et enseignements du forum

Newsletter - Coasters Association (2020)
Number of pages: 4

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Profil de la jeunesse anglophone de la Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Ce profil de la situation de la jeunesse anglophone de la Gaspésie et des Îles-de-la-Madeleine a été commandité par trois organisations communautaires : le Comité pour l’action sociale anglophone (CASA), le Conseil des Madelinot·e·s anglophones (CAMI) et Vision Gaspé-Percé Now. Des travaux de recherche-action fondés sur une approche participative et communautaire ont servi de base au développement de ce profil. Ce faisant, l’étude sur laquelle le présent document se fonde permet d’avoir un portrait des réalités propres à la jeunesse, développé par les jeunes elleux-mêmes; ceci permettra de travailler plus efficacement à la résolution des enjeux et des difficultés auxquels ils et elles font face dans les différentes communautés de la région. Une méthode d’approche mixte a ainsi été développée via la combinaison d’une enquête en ligne et de groupes de discussions sur des sujets liés à l’émigration, à l’éducation, à l’emploi, à la vie sociale, aux services, etc. Au total, 438 jeunes de 15 à 35 ans ont participé à l’enquête en ligne, et neuf groupes de discussion ont été instaurés sur un total de six communautés regroupant 82 jeunes.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Transferable Skills & Your 2020 Job Search - Voice of English-speaking Quebec (VEQ); Youth Employment Services (YES) (2020)

Annual Report 2019-2020 : Broadening Access for Better Futures - Youth Employment Services (YES) (2020)

Who We Are - Youth Employment Services (YES) (2020)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Closing the 12k Gap : Improving Employment for Quebec's English Community - Conference Report - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Youth Employment Services (YES) is pleased to have secured funding from the Secretariat for relations with English-peaking Quebecers (SRQEA) to build a stronger network of English service organizationsworking in employability. The Provincial Employment Roundtable (PERT) project aims to address three important employment issues facing English speakers in Quebec.

Combler l'écart de 12 000 Emplois : améliorer l'emploi pour la communauté d'expression anglaise du Québec - rapport de conférence - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Services d’emploi pour les jeunes (YES) est heureux d’avoir obtenu du ﬁnancement du Secrétariat des relations avec les Québécois anglophones (SRQEA) aﬁn de bâtir un réseau plus solide d’organismes de services en anglais qui travaillent dans le domaine de l’emploi. Le projet de la Table ronde provinciale sur l’emploi (PERT) a pour objectif d’aborder trois questions importantes en matière d’emploi auxquelles doivent faire face les anglophones au Québec.

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)
Number of pages: 5

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Parallel title: QUESCREN Working Paper no.1
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Parallel title: Document de travail QUESCREN no.1
Keywords: Official Language Minority Community (OLMC)

15 Years of ELAN - English Language Arts Network (ELAN) (2019)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

Practice Makes Perfect - Voice of English-speaking Quebec (VEQ) (2019)
Parallel title: Language Training Resources

The South Shore of Montérégie-Centre : Towards a Portrait of the English-speaking Community - Assistance and Referral Centre (ARC); Richardson, Mary (2019)

Promoting Opportunities for Youth Community Partnerships : A Policy Brief - Lai, Edward; Winrow, Adrienne; Orme, Charlie (Youth for Youth Québec (Y4Y Québec), 2019)
Across Canada, youth retention and success have always been key in ensuring the continued vitality of official language minority communities (OLMCs). Within the context of Quebec, retention in particular is a constant challenge, where English-speaking youth are disproportionately apt to pursue professional opportunities outside of the province. While this option should never be condemned, it is nonetheless important to ensure that those who wish to remain have access to the resources necessary to help them thrive therein. With this in mind, and considering that youth retention is equally beneficial to the state, policymakers need to be in a position to support organizations that are working towards this objective.
Keywords: Official Language Minority Community (OLMC)

Careers in Mental Health - Assistance and Referral Centre (ARC) (2019)

Careers in Nursing - Assistance and Referral Centre (ARC) (2019)

Technical Medical Careers - Assistance and Referral Centre (ARC) (2019)

Therapy & Rehabilitation Careers - Assistance and Referral Centre (ARC) (2019)

Employability Initiatives : 2019-2021 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Annual Report 2018-2019 / Rapport annuel 2018-2019 - Youth Employment Services (YES) (2019)
Keywords: Official Language Minority Community (OLMC)

English-speaking Blacks in Quebec : Highlights from the 2016 Census - Floch, William (2018)

Noirs d’expression anglaise au Québec : faits saillants du recensement de 2016 - Floch, William (2018)

Évaluation du projet: project pilote d'aide à l'emploi en Gaspésie pour les jeunes d'expression anglase - Marrotte, Jayme (Committee for Anglophone Social Action (CASA), 2018)

Les communautés anglophones de la Gaspésie-Îles-de-la-Madeleine : Un profil régional - Committee for Anglophone Social Action (CASA) (2018)

English-speaking Communities of the Gaspésie – Îles-de-la-Madeleine: A Regional Profile - Richardson, Mary; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)

Youth Internships in Community Media : A First Step Towards Capacity Building for Official Language Community Media in Minority Setting - Consortium of Official Language Minority Community Media (2018)
Keywords: Official Language Minority Community (OLMC)

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)
issued: January, 2018/August, 2018

Employee Resource Guide - NDG Community Council (NDGCC) (2018)

Guide de ressources d'emploi - NDG Community Council (NDGCC) (2018)

Recommendations from the Youth Unemployment Forum Held on December 5, 2017 - Youth Employment Services (YES) (2018)
In Quebec and indeed across Canada we are confronting the many and varied challenges of a rapidly evolving labour market. New technologies are developing at a rate that is challenging our institutions; globalization is bringing increasing unpredictability to economic systems; traditional management models are being disrupted by the growing sharing and gig economies. Youth may have adapted quickly to high-tech society, however it would be disastrous to assume they will adjust as easily to the trials of the Fourth Industrial Revolution. Today’s youth need innovative supports to help them to survive in and capitalize on the complexities of the future economy. While Québec youth have never been more highly educated or bilingual, young job seekers andemployers alike are frustrated. Not enough has been done to curb the outmigration of educated youth nor to create an equitable environment for underrepresented populations. It hardly matters that jobs may be available, if youth are not here or not able to connect with them. This is why, with support from Canadian Heritage, on December 5th, 2017 YES convened a daylong forum bringing together multiple sectors from throughout the province of Quebec, to develop a deeper understanding of the unique employment barriers faced by Quebec’s Official Language Minority Community (OLMC) youth.
Keywords: Official Language Minority Community (OLMC)

Demographic Profile of the English-speaking Communities : Administrative Region of Montréal & the Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Abitibi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC La Vallée-de-l'Or - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Rouyn-Noranda - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Bas-Saint-Laurent & MRC Rimouski-Neigette - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Côte-de-Beaupré - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Jacques-Cartier - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Portneuf - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Drummond - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Caniapiscau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Le Golfe-du-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Manicouagan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Sept-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Coaticook - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Granit - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Haut-Saint-François - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Val-Saint-François - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Les Sources - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Memphrémagog - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Avignon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Bonaventure - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC La Côte-de-Gaspé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Le Rocher-Percé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Les Îles-de-la-Madeleine - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC D'Autray - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Joliette - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Matawinie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Montcalm - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC La Rivière-du-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Pays-d'en-Haut - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Thérèse-de Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laval & the Rest of Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC La Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Maskinongé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Shawinigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Trois-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Beauharnois-Salaberry - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC Brome-Missisquoi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC La Haute-Yamaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.
Keywords: Official Language Minority Community (OLMC)

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC La Vallee-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Le Haut-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Le Haut-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Les Jardins de Napierville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Les Maskoutains - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Longueuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Marguerite-d'Youville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC Pierre-de Saurel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.
Keywords: Official Language Minority Community (OLMC)

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Rouville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC La Vallee-de-la-Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Les Collines-de-l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Papineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Pontiac - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Saguenay-Lac-Saint-Jean & MRC Saguenay - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Impact of the 2011-2014 Community Leadership Bursary Program : Adjustments for the future? - Gagnon, Marie-Pierre; Lampron, Amélie (2018)

Main Achievements 2014-2018 - Dialogue McGill (2018)

Profil des rélisations 2014-2018 - Dialogue McGill (2018)

Job Posting : Events & Access Coordinator - State of the Arts III - English Language Arts Network (ELAN) (2018)

Job Posting : Project Manager - State of the Arts III - English Language Arts Network (ELAN) (2018)

Demographic Profiles of English-speaking Communities : RLS de la Baie des Chaleurs (1111) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
issued: 2017/2018
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RLS de la Cote de Gaspe (1113) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
issued: 2017/2018
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RLS du Rocher Perce (1114) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
issued: 2017/2018
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS de l'Abitibi (0812) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Gaspesie (1110) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre & RLS de Champlain (1611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 7

Programme de maintien en poste : Monitoring des stagiaires - Storr, Caroline; Hendrickson, Mary (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)

Final Report: Emploi Quebec: Coasters Association - Gallibois-Robertson, Melanie (Coasters Association, 2017)

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)
issued: January, 2017/August, 2017

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 4

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

Demographic Profiles of English-speaking Communities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches (1210) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS Alphonse-Desjardins (1211) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de Beauce (1213) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de la région de Thetford (1212) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS de Rouyn-Noranda (0813) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS du Témiscaming (0815) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS Vallée-de-l'Or (0814) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Hochelaga - Mercier-Ouest - Rosemont (0653) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Rivière-des-Prairies - Anjou - Montréal-Est (0652) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Saint-Léonard - Saint-Michel (0651) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS d'Asbestos (0517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Coaticook (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Haute-Yamaska (0512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Pommeraie (0511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Sherbrooke (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Val Saint-François (0516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Granit (0519) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Haut-Saint-François (0518) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie & RLS de Memphrémagog (0513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Dorval - Lachine - Lasalle (0612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Pierrefonds - Lac Saint-Louis (0611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de Grande-Rivière - Hull - Gatineau (0714) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Gatineau (0712) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Lièvre et de la Petite-Nation (0715) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS des Collines-de-l'Outaouais (0713) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS du Pontiac (0711) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Portneuf (0311) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Québec-Sud (0312) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS Québec-Nord (0313) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Kawawachikamach (0917) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Basse-Côte-Nord (0916) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Haute-Côte-Nord - Manicouagan (0912) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Sept-Îles (0914) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS d'Arthabaska-de l'Érable (0418) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Bécancour - Nicolet-Yamaska (0416) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Trois-Rivières (0415) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Haut-Saint-Maurice (0411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre (1610) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre & RLS du Haut-Richelieu - Rouville (1612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est (1620) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS de Richelieu-Yamaska (1622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-Boucher (1621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-de Saurel (1623) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest (1630) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Jardins-Roussillon (1634) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Vaudreuil-Soulanges (1631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Haut-Saint-Laurent (1633) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Suroît - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière (1410) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Nord (1411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Sud (1412) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Laval (1310) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides (1510) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Antoine-Labelle (1511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Argenteuil (1514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Deux-Montagnes - Mirabel-Sud (1515) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de La Rivière-du-Nord - Mirabel-Nord (1516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Thérèse-de Blainville (1517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Laurentides (1512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Pays-d'en-Haut (1513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent & RLS de Rimouski (0115) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-des-Neiges - Métro - Parc-Extension (0622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-Saint-Luc - NDG - Montréal-Ouest (0621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS de Verdun - Côte St-Paul - St-Henri - Pointe-St-Charles (0631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS des Faubourgs - Plateau-Mont-Royal - St-Louis-du-Parc (0632) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS d'Ahuntsic - Montréal-Nord (0642) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS de la Petite Patrie - Villeray (0643) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS du Nord de l'Île - Saint-Laurent (0641) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Chicoutimi (0215) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Jonquière (0214) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de La Baie (0216) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)
issued: January, 2016/August, 2016

Poverty and Social Exclusion in Quebec's English-speaking Communities : a Brief Submitted by the Community Health and Social Services Network (CHSSN) in Contribution to the Development of the Third Action Plan to Combat Poverty and Social Exclusion by the Government of Quebec - Community Health and Social Services Network (CHSSN) (2016)
A Brief submitted by the Community Health and Social Services Network (CHSSN) in contribution to the development of the third Action Plan to combat poverty and social exclusion by the Government of Quebec.
Keywords: Official Language Minority Community (OLMC)

Key Socio-demographic Characteristics of English-speaking Children, 2011 Gaspésie – Îles-de-la-Madeleine and Census Divisions - Pocock, Joanne (2016)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

McGill Retention of Health Professionals Project : Community Organization Descriptions 2015 - 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

English-speaking Seniors : RTS de l'Estrie - CHUS - Townshippers' Association (2016)

Fall 2016: Program Book : September 2016 - December 2016 - Youth Employment Services (YES) (2016)

McGill Program Networks Creating Impacts - Buffitt, Kimberly (2015)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

Workforce of Tomorrow Youth Skills Link Project - Buckle, Heidi (Coasters Association, 2015)
The Coasters Association implemented a fourth phase of the Youth Skills Link Project which began on May 18th, 2015, and ran until November 13th, 2015, funded by Service Canada. The YSLP entitled: “Workforce of Tomorrow” was designed to help out eight (8) youth between the ages of 15-30 throughout the Lower North Shore, to overcome employment barriers by enabling them to develop/improve on self-knowledge, employability skills, skills enhancement, through three weeks of Group Based Employability Skills training, and seventeen (17) weeks of work experience. The project was posted throughout the coast inviting youth to take part in the project based out of their respective communities/municipalities. A total of seven (7) applicants were received, interviews were carried out with each applicant and job placement was necessary before final selection. The selected youth derived from the Municipalities of C te Nord du Golfe du Saint Laurent, Gros Mecatina, Bonne Esperance, and Blanc Sablon were hired for twenty (20) weeks of training and work experience.

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Building a Career as an Artist - Macdonald, Amy; Shaughnessy, Kyra (2015)

Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Mesure 2 : Programme de maintien en poste : Volets Réseaux communautaires et Maisons d’enseignement : Prospectus 2014-2018 - Dialogue McGill (2014)
Le Projet de formation et de maintien en poste des professionnels de la santé de l’Université McGill contribue aux initiatives du Québec destinées à assurer aux Québécois d’expression anglaise l’accès dans leur langue à la gamme complète de services de santé et de services sociaux, et ce, au moyen de diverses mesures visant à fournir et à maintenir en poste un complément de main-d’œuvre suffisant, capable d’offrir des services en anglais. Le projet constitue un outil additionnel favorisant l’application et la bonification des programmes régionaux d’accès aux services de santé et aux services sociaux en langue anglaise, conformément à la Loi sur les services de santé et les services sociaux. Ce Projet a pour objectifs précis de susciter des initiatives de formation et de maintien en poste qui fourniront aux professionnels de la santé et des services sociaux l’occasion d’améliorer leur capacité d’offrir des services en anglais, ainsi que l’occasion de travailler là où ils seront en mesure de répondre aux besoins des populations d’expression anglaise du Québec. Le Projet vise également à promouvoir la recherche et le partage de l’information quant aux approches visant à réduire les barrières en matière d’accès aux services de santé et aux services sociaux pour les Québécois d’expression anglaise.

Retention Program for the McGill University Training and Retention of Health Professionals Project : Evaluation of the retention program measure and recommendations - Gagnon, Marie-Pierre (Dialogue McGill, 2014)
This report presents an evaluation of the activities implemented under the Retention Program, in relation to the Support for Health and Social Services Institutions and Support for Educational Institutions in order to highlight the main strengths and areas for improvement. The mandate was to identify strategies that could help to increase the impact of the internship program on the retention of health and social services professionals in the health and social services network. The evaluation would then contribute to the ongoing improvement of this program, by providing some direction to guide the actions of those responsible for the McGill University Training and Retention of Health Professionals Project and project partners.

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 7

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)

Language Training Program : Overall Profile 2009-2013 : Discussion Guide - Dialogue McGill (2013)

Language Training Program : Overall Profile 2009-2013 - Dialogue McGill (2013)
The Language Training Program, Measure 1, has three components. The first two pertain to English and French for professional purposes courses offered through the regional language training projects designed and implemented by Quebec’s 18 health and social services agencies (the "agencies"). The third covers support activities for the trainers giving language courses in the regions and the learners who take those courses. These activities are developed and offered by the McGill Project team. The Program structure and content were developed by the McGill Project team and are described in Language Training Program – Frame of Reference 2009-2013, which also describes the target users; the Program objectives, partners and conditions; the parameters of the call for proposals for regional training projects; and regional allocation of the funding envelope. A coordinating mechanism, the MSSS-McGill Joint Committee, implements and monitors the Program, as prescribed in the Implementation Framework that the two organizations signed onto in November 2009.

Programme de Formation Linguistique : Profil global 2009-2013 - Dialogue McGill (2013)
Le Programme de formation linguistique, Mesure 1, comporte trois volets. Les deux premiers font référence à des cours d’anglais et de français, langue professionnelle, qui sont offerts dans le cadre des projets régionaux de formation linguistique conçus et mis en œuvre par les 18 agences de la santé et des services sociaux (les « agences »). Le troisième regroupe des activités de soutien destinées aux formateurs qui donnent des cours de langue en région et aux apprenants qui y participent. Ces activités sont développées et offertes par l'équipe du Projet McGill. La structure et le contenu du Programme ont été élaborés par l’équipe du Projet McGill et sont décrits dans le document Programme de formation linguistique - Cadre de référence 2010-2013, tout comme le sont la clientèle visée, ses objectifs, ses partenaires, les conditions à respecter, les paramètres de l’appel de propositions des projets régionaux de formation et la répartition régionale de l'enveloppe budgétaire. Un mécanisme de coordination, le Comité conjoint MSSS-McGill, assure la mise en œuvre et le suivi du Programme comme le prévoit le Cadre de mise en œuvre convenu entre les deux organisations, en novembre 2009.

Training and Retention of Health Professionals Project : Research development program : overall profile 2009-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services. The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). This report is the third in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series deals with the three measures of the McGill Project, namely, the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program. The reports are organized to reflect the structure of each program as set out in the reference documents. Each report begins with an introduction of the program, then briefly describes the variables, data sources and sections of the report. This document reports on Measure 3, the Research Development Program, and is meant to inform Program reframing in Phase 3 (2013-2018).

Training and Retention of Health Professionals Project : Retention program : overall profile 2011-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services . The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social This report is the second in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series concerns the three measures of the McGill Project, namely, services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program.

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.

Building Youth Resiliency and Community Vitality Within Montreal’s English Language Population : The YES Experience with Youth Seeking to Improve their Work Situation - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2013)
In response to an increase in the number of clients’ experiencing mental health challenges in the course of their job search YES (through CHSSN) has commissioned this report to establish an evidence-based profile of the youth that they serve. At the present time, YES uses limited resources to offer additional support through a focus group that is designed for clients who are experiencing symptoms such as decreased motivation, anxiety, social isolation and diminished confidence in dealing with the transition process.
Keywords: Official Language Minority Community (OLMC)

Report : Community Network Forum : Enhancing Resiliency to Overcome the Challenges of Work and Personal Stress - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
A forum on approaches to promoting resilience to turn strengths into strategies to restore abilities to cope and adapt to stress in work and personal situations for ourselves and the communities we serve.

Program Book - Youth Employment Services (YES) (2013)
issued: Winter, 2013/Spring, 2013

Winter/Spring 2013 Program Book - Youth Employment Services (YES) (2013)

YES' Artists' Conference: Business Skills for Creative Souls - Youth Employment Services (YES) (2013)

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Regional Development of English Language Entrepreneurial Services - Qu'anglo (Youth Employment Services (YES), 2012)
YES is a non-profit organization that provides English language employability and entrepreneurship services in Quebec, principally those on the Island of Montreal. The areas of services offered are job search, entrepreneurship, mentorship and artists’ programs. In response to requests from the organizations in the regions outside of Montreal for similar services, YES has begun to develop support and delivery mechanisms that respond to the unique needs of the regions1 within a context of building economic viability. This report provides the results of the work carried out in 2011-12 to look at the feasibility of offering YES-type services in the regions, as well as the planning and development activities that should be carried out to support a broader economic development amongst English-speaking communities in Quebec.
Keywords: Official Language Minority Community (OLMC)

ACCORD Sample Contract - English Language Arts Network (ELAN) (2012)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

Entrepreneurship & Artists' Online Program : Winter/Spring 2012 - Youth Employment Services (YES) (2012)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

9th Quebec Employment Service Providers Conference : The Greatest Challenges and Best Practices of Employment Service Professionals - Youth Employment Services (YES) (2011)

Language Training Program : Frame of Reference 2010-2013 - Dialogue McGill (2011)
The McGill Training and Retention of Health Professionals Project seeks to contribute to Government of Quebec initiatives aimed at ensuring that English-speaking Quebecers have access to the full range of health and social services in their language. To this end it proposes a series of measures to train, hire and retain an adequate workforce for delivering health services and social services in English. The Project objectives are to a) improve the capacity of the health and social services network to serve English speakers in their language and b) increase the participation of English-speaking professionals in Quebec’s health and social services system. The achievement of these goals depends on a solid partnership between McGill University and the ministère de la Santé et des Services sociaux (MSSS). A MSSS-McGill joint committee has been formed to oversee the implementation and monitoring of the various Project measures.

Programme de formation linguistique : Cadre de référence 2010-2013 - Dialogue McGill (2011)
Le Projet de formation et de maintien en poste des professionnels de la santé de l’Université McGill se veut une contribution aux initiatives du gouvernement du Québec pour assurer aux Québécois d’expression anglaise l’accès dans leur langue à la gamme de services de santé et de services sociaux. À ce titre, le Projet propose diverses mesures visant à former, à embaucher et à maintenir en poste une main-d’œuvre suffisante capable d’offrir des services de santé et des services sociaux en anglais. Les objectifs du Projet sont d’améliorer la capacité du réseau de la santé et des services sociaux de répondre aux besoins des personnes d’expression anglaise dans leur langue et d’accroître la participation des professionnels d’expression anglaise dans le système québécois de santé et de services sociaux. L’atteinte de ces objectifs repose sur un partenariat entre l’Université McGill et le ministère de la Santé et des Services sociaux. Un comité conjoint MSSS-McGill est formé afin d’assurer la mise en œuvre et le suivi de l’ensemble des mesures du Projet.

New Online Service Makes Expert Advice Accessible and Affordable - Youth Employment Services (YES) (2011)

Briefs Submitted to the Minister of Education, Recreation and Sports : 2011 - Advisory Board on English Education (2011)

Lower North Shore Youth Employability Forum - Fequet Griffin, Priscilla (Coasters Association, 2011)
The 2011 Lower North Shore Youth Employability Forum was coordinated to provide the youth on the Lower North Shore with a two day intensive training on employability skills and provide them a forum to discuss with our Council of Mayors and leading community organizations and institutions the labour force market on the Lower North Shore. The projected outcome of the forum was to expand youth’s awareness of the shortages in labour in certain skilled trades sectors of employment and to improve opportunities for youth living in smaller, rural communities where jobs and employment services are more difficult to find. Thus, the skills developed during the two day forum will allow youth to further develop their capacity to enter into the labour force and raise awareness around labour opportunities on the Lower North Shore.

Training and Human Resources Development Project : Final Report - Dialogue McGill (2010)
McGill University’s 2004-2008 Training and Human Resources Development Project sought to contribute to improving English-speaking Quebecers’ access in their own language to the range of health and social services offered to the general population. The 2004-2008 Project was funded through Health Canada’s program to support Quebec initiatives for improving access to health care and social services for English speakers. It was sponsored by McGill University’s Faculty of Arts and administered by its English and French Language Center in conjunction with its School of Social Work. The budget allocated for the 2004- 2008 period was $ 11,757,828. The project had two objectives: to ensure effective communication between English-speakers and the health and social services workers serving them and to increase the participation of English-speaking professionals in the Quebec health and social services network.

Evaluation and Rating Report of English-French Guide to Human Services terminology / Guide français-anglais de la terminologie des services à la personne - Lexicon Evaluation Committee; Harrison, Sue (2010)

[Letter to the Minister Concerning Issues of Inclusion and Integration in the Classroom] - Advisory Board on English Education (2010)

[Lettre au ministre concernant l'inclusion et intégration en classe] - Advisory Board on English Education (2010)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

Socio-Economic Profiles of Quebec’s English-speaking Communities: Companion Report to the CHSSN online table series - Pocock, Joanne; Warnke, Jan; Carter, James (Community Health and Social Services Network (CHSSN), 2010)
The Companion Report to the CHSSN online Socio-economic Profiles explores the current situation of Quebec’s English-speaking communities with respect to three related social determinants of health namely, income, employment and education.

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

Projet de formation et de développement des ressources humaines : Rapport annuel - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)
Number of pages: 2

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)
Number of pages: 4

YES E-News : April 2009 - Youth Employment Services (YES) (2009)
Number of pages: 1

Transformation Through Lifelong Learning: A Path to Change - Quebec Association for Adult Learning (QAAL) (2009)

Dialogue : Better Communication for Better Care - Dialogue McGill (2009)
Number of pages: 4

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2009)
Number of pages: 3

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

Congrès des Fournisseurs de Sercices d'emploi du Québec (2008)

Quebec Employment Service Providers Conference (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Lost in Translation - Buffitt, Kimberly; Lanyi, Danille (2008)

The Training and Retention of Health Professionals Project - Dialogue McGill (2008)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

Stepping into the Future : L’avenir entre nos mains - Carrefour jeunesse-emploi NDG; Table de concertation jeunesse NDG (NDG Community Council (NDGCC), 2008)
Community‐based planning to facilitate the socio‐professional integration of youth between the ages of 16 ' and 30 in Notre‐Dame‐de‐Grâce, Côte‐Saint‐Luc, Hampstead and Montreal‐West. A project of the Carrefour jeunesse‐emploi NDG and the Table de concertation jeunesse NDG, in collaboration with Service Canada

Dialogue : Better Communication for Better Care - Dialogue McGill (2008)
issued: Spring, 2008/Summer, 2008 Number of pages: 7

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2008)
issued: Spring, 2008/Summer, 2008 Number of pages: 5

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

Discussion Document #1 : Demographics and the Long-term Development of the English-speaking Communities of the Greater Montreal Region - Quebec Community Groups Network (QCGN); Greater Montreal Community Development Initiative (GMCDI) (2007)

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.
Parallel title: Measure 2 : Retention and Distance Professional and Community Support Program November 6 2006 to March 31 2007

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

Dialogue : Better Communication for Better Care - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 7

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 5

Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)

Special Needs Project - Lavallée, Marissa (2007)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

Self-Employment and Employment in Quebec's English-speaking Cultural Communities and Visible Minorities : Prospects and Problems - Jedwab, Jack (Youth Employment Services (YES), 2006)
What are the principal barriers to self-employment and employment for members of Quebec’s English-speaking visible minorities and cultural communities? The question is considered in this report in view of the ongoing challenges that some members of English-speaking visible minorities and cultural communities face in the current economy. The specific aim is to improve our understanding of factors which prevent members of Quebec’s English-speaking visible minorities and cultural communities from achieving self-employment and employment goals.

Language Training Program : Findings and recommendations of the lexicon evaluation committee - McLaughlin, Sky; Rogers, Jim (Lexicon Evaluation Committee, 2006)

Skills and Thrills - Gallibois, Kris (Coasters Association, 2006)
The main goal of this project was to develop leadership skills in the youth in St. Augustine ages 12-17. I held meetings with the youth, conducted workshops on leadership and decision making skills, decided upon a goal to accomplish and a plan to carry out the said goal. Also, I held fun sessions wherein the youth participated in activities and games.

A Needs Assessment on the Issue of Hiring and Retaining English Professionals on the Lower North Shore - Coasters Association (2006)
The Coasters Association, in partnership with the Centre de Santé et de Services Sociaux de la Basse- Côte-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University for seven (7) weeks from February 13 to March 31, 2006, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining Professionals, not only English-speaking - but Bilingual Professionals as well, on the Lower North Shore of Quebec. The objective of this needs assessment was to develop Phase II which is a two year proposal that would lead to the improvement of hiring and retaining professionals on the territory. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the Lower North Shore. Another objective of this needs assessment is to make contact with institutional and community based organizations (ie: Education and H.&S.S.), it is hoped that these contacts will lead to long term partnerships and commitment to addressing the hiring and retention of English and/or Bilingual Professionals on the Lower North Shore.

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)
Number of pages: 7

6th Montreal Self-Employed Artists Conference - Youth Employment Services (YES) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)
Number of pages: 6

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)
Number of pages: 7

Training and Human Resources Development Project : Measure 1 : Language training program - Dialogue McGill (2005)
The language training program presented is part of the Training and Human Resources Development Project that McGill University is to implement. This project is designed to ensure that English-speaking Quebecers obtain equitable access, in their language, to the range of health and social services offered to the entire population. The project has been elaborated against a backdrop of sociodemographic changes affecting Québec’s English-speaking communities, the adoption of new legislation modifying the organization of work, and the modernization of the health and social services system. It will be geared to clinical projects now being prepared pertaining to the organization of services. The project is an additional means of reviewing and implementing regional programs of access to health and social services in the English language, as stipulated by the Act respecting health services and social services.

The Development of an Action Plan to Expand Volunteerism & Leadership on the Lower North Shore of Quebec - Buckle, Heidi (Coasters Association, 2005)
Throughout phase one of this project, a needs assessment study was successfully carried out to identify the needs of the one hundred and thirteen (113) community organizations and twenty-one (21) regional organizations on the coast; along with a volunteer awareness campaign and the building of a strong volunteer base for the fifteen (15) communities of the Lower North Shore of Quebec. This study was then distributed to all the organizations, the working group, the Board of Directors of the Coasters Association and the volunteers who participated in this project. It has been shared with various Quebec Community Group Networks and HRD Community Table groups across the province, along with various federal and provincial government departments. It has been used as a working tool by many organizations on and off the coast.

The English-speaking Catholic Population Profile in Quebec, 2001 : Comparative Analysis of the Demographic Characteristics and Geographic Distribution of the FOLS-English Catholic Population in Quebec - Ahmadzadeh, Nazanin (English Speaking Catholic Council, 2004)
The general objective of this study is to provide the English-Speaking Catholic Council in Québec with a comprehensive demographic portrait of the English speaking Catholic Community in Québec. This portrait will serve as support for the orientation of the ESCC. This study follows a previous study carried out in 1992 which focused only on the parishes in the Montreal metropolitan area.

The English-Speaking Catholic Population in Quebec, 2001 - Ahmadzadeh, Nazanin; Warnke, Jan (2004)

A Report on the Quebec Fishing Community Adjustment Measures (QFCAM) Project - Blanche, Diana (Coasters Association, 2003)
The following report is a compilation of information pertaining to the activities under taken by the participants of the Fishery Restructuring Program.

Global Development Plan : Strategy to Revitalize the English-language Minority Communities of Quebec : Sector Plans - Quebec Community Groups Network (QCGN) (2003)
The roots of the English-speaking community in Quebec go back nearly 250 years, and have a historic place in the development of the province. While English-speaking communities traditionally established their own institutions in the areas of religion, education and health and social services, that type of community engagement dissolved to a greater extent with the Quiet Revolution and the emergence of the modern Quebec state. Now, after 30 years of exodus and isolation, the time has come for the English-speaking community to become involved, to re-establish its presence in the policy and program decision-making areas that affect the daily lives of its members.

Global Development Planning : Strategy to Revitalise the English Language Minority Communities of Quebec : Education & Training - Quebec Community Groups Network (QCGN) (2003)
The following Plan has been prepared by the Education & Training Task Force - one of eight sector task forces which bring together leading representatives from across the Province committed to the preparation of a Global Development Plan for the Englishspeaking minority communities of Quebec.

Leadership Handbook - Quebec Federation of Home and School Associations (QFHSA) (2003)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Alliance Quebec Presents Equity Brief to Quebec National Assembly - Alliance Quebec (AQ) (2000)

Brief on Draft Law Number 143 Equity in the Civil Service - Alliance Quebec (AQ) (2000)
As the Committee studying draft law 143 is aware, Alliance Quebec is an association which lobbies governments at all levels for the rights and needs of the Englishspeaking population of Quebec to be respected. Our organization has chapters in Montreal, West Island, East Island, South Shore, Laval, Rouyn-Noranda, Val d'Or, Saguenay Lac Saint Jean, Mauricie and the Upper and Lower Laurentians. We also have our provincial youth commission that represents young people province-wide. In all, over 83 percent of Quebec's English-speaking population resides in Alliance Quebec territory.

Alliance Quebec Supports Superior Court Ruling on Computer Software Case - Alliance Quebec (AQ) (2000)

Conference on Job Equity and Employability - Johnson, William (2000)

A Brief on Quebec's English-speaking Youth on the Occasion of the Youth Summit - Alliance Quebec (AQ) (2000)
We, the English-speaking youth of Quebec, come before you today to ask that our distinctive voices be heard. We share many of the concerns, problems and preoccupations of our French-speaking brothers and sisters. But we have anguishes, specific and poignant, which are ours alone, and which you will not hear about from the other participants and observers at the Youth Conference.

Border Labour Situation a Threat, Johnson Warns Quebec - Alliance Quebec (AQ) (1999)

Alliance Quebec Youth Seek Meeting with Premier - Alliance Quebec (AQ) (1999)

Alliance Quebec Denounces an Alarmist La Presse Story - Alliance Quebec (AQ) (1999)
Parallel title: Louise Beaudoin Uses Such Statistics to Justify Tightening the Screws

[Letter from Pat Courcelle, President of Société franco-Manitobaine and Michael J. Hamelin, President of Alliance Quebec, to Rt. Hon. Jean Chrétien, Prime Minister of Canada] - Courcelle, Pat; Hamelin, Michael J. (1997)

Agreement on Manpower Development a Positive Step - Alliance Quebec (AQ) (1997)

Transfer of Manpower Could Sacrifice Essential Protections for Minority-Language Services and Information : AQ - Alliance Quebec (AQ) (1997)

Alliance Quebec Worried About Federal-Provincial Manpower Talks - Alliance Quebec (AQ) (1996)

Alliance Québec - Une nouvelle étude sur la langue vise-t-elle les institutions anglophones et les gens qui y travaillent? - Alliance Quebec (AQ) (1996)

Francisation en milieu de travail - Alliance Quebec (AQ) (1993)
En 1977, au moment de l'application de la Loi 101, on se préoccupait beaucoup de la quantité et de la qualité du travail effectué en français au Québec. La Commission Gendron avait auparavant indiqué que 82 % de toutes les communications écrites se faisaient en anglais, au Québec. En vertu de la Loi 101, toutes les entreprises établies au Québec et comptant 50 employés ou plus sont tenues de fonctionner en français. Elles doivent posséder un «certificat de francisation» prouvant que tel est le cas. Quand la Loi 101 fut adoptée, la plupart des entreprises ont eu quatre ans pour s'y conformer.

Alliance Quebec Brief to the Standing Committee on Cultural Communities & Immigration on the Charter of the French Language - Alliance Quebec (AQ) (1983)
More than a year and a half dgo, the Premier of this province publically called for a dialogue on Bill 101. He stated the hope that the dialogue would be fruitful, and that it would be marked by reasonableness and good faith on the part of everyone concerned. Alliance Quebec, which from the beginning of its existence has proven its commitment to reasonab'l eness and good faith, remains convinced that Quebecers can attain a fair, meaningful and pr oductive resolution of the language debate. This is a debate which has continued for too long, consuming or diverting energy, provoking friction and causing in human terms, considerable damage and loss. We can Iive together, French-speaking and Enlish-speaking Quebecers, in dignity, security and mutual respect; the obstacles are not insurmountable and it is time that they were removed.

A Policy for the English-speaking Community of Quebec - Alliance Quebec (AQ) (1982)
We are almost one million English-speaking Quebecers. We regard Quebec as our home. Our community has participated in more than two hundred years of Quebec's history. We have contributed to the building of one of the world's most stable, prosperous and culturally rich societies. We believe that the interplay of the influences of Quebec's French-speaking and English-speaking peoples has been mutually enriching.

Recommendations for a New System for the Negotiation of the Collective Agreements of School Boards and Regional Boards : Brief submitted to the Commission of Study and Consultation on the Revision of the System of Collective Barganing in the Public and Para Public Sectors by the Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1977)
The Quebec Federation of Home and School Associations, formerly known as the Quebec Federation of Protestant Home and School Associations (hereinafter referred to as "Quebec Federation") is pleased to have the opportunity to present to the Martin Commission the views of its membership concerning the Teacher Contract Negotiations.

Brief on Teacher Classification Presented by Quebec Federation of Home & School Associations to Commission of Study on the Classification of Teachers - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations at its Annual General Meeting held in May 1971, passed two resolutions on the issue and conflict arising in respect of Teacher Classification to be directed to the Minister of Education.

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1967)
Number of pages: 8

The Employment and Socio-demographic Profile of English-speakers in Roussillon : Presenting a community portrait on employment of English-speaking residents of Roussillon - Assistance and Referral Centre (ARC)

It is OK to Speak Up : Know Your Rights in the Workplace - Black Community Resource Centre (BCRC)

Your Rights at the Workplace - Black Community Resource Centre (BCRC)

CEDEC Brand Handbook - Community Economic Development and Employability Corporation (CEDEC)

CEDEC : Career Focus Project Ideas - Community Economic Development and Employability Corporation (CEDEC)

Earn While you Learn Sutton : A CEDEC Collaboration Story - Community Economic Development and Employability Corporation (CEDEC)
Tourism is a major economic driver in the Sutton area, however, labour shortages are hampering growth. Through innovative skills training, tourism sector employers are attracting new talent and through upskilling they are retaining and promoting their existing workforce to take on new responsibilities and secure year-round employment.

Manuel de la marque de commerce de la CEDEC - Community Economic Development and Employability Corporation (CEDEC)

NPI Leadership Development : Enhancing the Leadership Capacity of Minority English-Language Community Health and Social Services Networks (NPls) in the Province of Quebec - Community Health and Social Services Network (CHSSN)

Perfectionnement en leadership des NPI : Renforcer les capacites de leadership des minorites de langue anglaise des reseaux communautaires de sante et de services sociaux (NPI) du Quebec - Community Health and Social Services Network (CHSSN)

The Black Community Resource Centre and the Provincial Employment Rountable Present : The Education to Employability Webinar - Davids, John; Fang, Xiaoyan; Gagnon, Morgan

Job Hunting Tips for Introverts - Khamala, Maya

The "Candidate Experience" Evaluation the Hiring Process - Khamala, Maya

Competency-Based Progress Assessment Skills for Life-long Learning - Literacy Quebec (LQ)

Mental Health and the Work Place : It's Okay to Not Feel Okay - Morgenstern-Clarren, Rachel

“Tell Me About Yourself" : How to Answer the Hardest Interview Question - Morgenstern-Clarren, Rachel

How to Obtain a Nursing Permit from the Ordre des Infirmières et infirmiers du Quebec - Ordre des Infirmières et infirmiers du Québec

PERT Trip : Les Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT)

Québec’s Best Language Training Practices in Action : Francisation du Mont Sutton - Provincial Employment Roundtable (PERT)

The Vision of the Social and Solidarity Economy Entrepreneurial Network (SEE Net) - Regional Development Network (RDN)

Youth Network - Réseau de l’est de l’île pour les services en anglais (REISA)

Provincial Employment Roundtable - Salter, Nicholas

Best Hiring Practices - Youth Employment Services (YES)

Employee Contract & Handbook - Youth Employment Services (YES)

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)

Making your Job Search Work for You - Youth Employment Services (YES)

Regional Resources for Employment - Youth Employment Services (YES)

Setting Up an Employee File - Youth Employment Services (YES)

The 10th Annual YES Entrepreneurship Conference : YES, The Future is Yours : Workshops - Youth Employment Services (YES)

The 19th Annual Entrepreneurship Conference - Youth Employment Services (YES)

YES E-News Monthly - Youth Employment Services (YES)
Number of pages: 1